Proses Kreatif Karya Tari Seri Fatwa - Silalahi, Mega Lestari; Asra, Rezky Gustian (Universitas Negeri Medan, 2025)
The Seri Fatwa dance inspired work by Malay literature, namely Gurindam Dua Belas, created by Raja Ali Haji. The contents of Gurindam Dua Belas consist of twelve chapters with moral messages for human life. This work began with the concept of a solo dance danced by Rezky Gustian Asra, then underwent renewal in the creative process of creating a group dance consisting of three dancers which became a new form of presentation. The embodiment of this group dance form was created for performances at the Siak Bermadah Riau Festival, then continued with the Bangka Season of Arts Festival, the Batam Kenduri Melayu Arts Festival and represented Indonesia in performances at the 2023 MAPEH conference at Suphanburi College of Dramatic Arts, Thailand. The journey of this dance work aims to bring Malay culture in the promotion and education of one of the Malay literary works, namely Gurindam 12. This research uses a qualitative approach with a descriptive analysis method, where the author carries out an analysis process from video documentation sources of performances, interviews and artistic reviews of works. This paper reviews the creative work process in creating and presenting Fatwa Series dance works.